Analisis Keterkaitan Tingkat Kepercayaan Pengguna Dalam Melakukan Transaksi Online (E-Commerce) Pada Instagram - Fida Royani; Ari Kusyanti; Himawat Aryadita (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The growth of internet users who are very significant to make many new things appear, one of which is trade transactions of goods and services over the internet. Instagram can provide benefits, the advantages in terms of doing business as a sales promotion and media. Indonesia ranks as the highest peak of the country's Internet users become victims of Cyber crime a vulnerable become victims of online crime. This study developed a framework for theories that explain what factors affect the level of trust in conducting online transactions through an account online shop on instagram. Samples obtained as many as 120 respondents. Later data analysis on the research of multiple linier regression using this. The results of this research show that the level of trust at the time of online transactions is influenced by the abundance of the perceived benefits of the user in fulfilling the needs or progression to follow or adapt current products , makes it easy for the buyer at the time of the transaction and the user feel safe at the moment provide personal information when making a transaction.